THE OLD NEW DISCIPLINE - Tatyana D. Venediktova (Высшее образование в России)
The author presents a review of Irina Korotkina’s new book Academic Writing: Process, product and practice (Moscow: Urait, 2015). The validity of the book’s content and methodology is regarded within the new trends in the Russian education and the emergence of academic writing as a new discipline, although it has a long history in the Western tradition, reflected in the book.